Soul Navigation For Entrepreneurs: Character Educations In Independent Curriculum Framework and Rahmatan Lil-Alamin Profile at Islamic High School - Alstra, Dilla; Susanti, Dessi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
Facing the challenges of globalization and technological advancements, developing entrepreneurial character is vital in shaping innovative, proactive, socially and ethically responsible individuals. This study aims to analyze the implementation of entrepreneurial character education through the independent curriculum and the Rahmatan Lil Alamin profile in students of state Islamic high schools to develop character and ethical values that support professional success and positive contributions to society. To create young entrepreneurs with responsible and faithful character, education in schools plays and essential role in forming entrepreneurial character. This research is a qualitative descriptive study, with the subjects being one principal and 29 teachers at State Madrasah Aliyah Insan Cendekia Padang Pariaman. The data used consisted of primary data (observations and interviews) and secondary data (information from literature studies). The data analysis process underwent the stages of collection, processing, and presentation of results. This study reveals that State Madrasah Aliyah Insan Cendekia Padang Pariaman has successfully implemented entrepreneurial character education by integrating entrepreneurial values into the curriculum, supported by experiential learning approaches and social interactions. Therefore, the conclusion showed that the Rahmatal Lil Alamin Curriculum was sufficiently implemented at MAN Insan Cendekia Padang Pariama.